2007
DOI: 10.1021/ja067631z
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Binding of Cisplatin to DNA:  Why Does Cisplatin Form 1,2-Intrastrand Cross-Links with AG But Not with GA?

Abstract: The bifunctional binding of the anticancer drug cisplatin to two adjacent nucleobases in DNA is modeled using density functional theory. Previous experimental studies revealed that cisplatin binding to adjacent guanine and adenine is sensitive to nucleobase sequence. Whereas AG 1,2-intrastrand cross-links are commonly observed, the analogous GA adducts are not known. This study focuses on understanding this directional preference by constructing a full reaction profile using quantum chemical simulation methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 78 publications
1
79
1
2
Order By: Relevance
“…[3][4][5] Extensive research has been reported which elucidates cisplatin's mechanism of action. 2,[6][7][8][9][10] Upon administration, the relatively high concentration of chloride ions in blood (~100 mM) maintains cisplatin in a neutral state. Inside the cell, the lower chloride ion concentrations (~4-20 mM) facilitate activation of cisplatin by stepwise aquation, and subsequent reaction with various cellular targets, most notably DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Extensive research has been reported which elucidates cisplatin's mechanism of action. 2,[6][7][8][9][10] Upon administration, the relatively high concentration of chloride ions in blood (~100 mM) maintains cisplatin in a neutral state. Inside the cell, the lower chloride ion concentrations (~4-20 mM) facilitate activation of cisplatin by stepwise aquation, and subsequent reaction with various cellular targets, most notably DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, theoretical and computational methods have increasingly supported the search for new platinum drugs. Cisplatin has been intensively studied at theoretical level from various aspects, including its structure [31], the hydrolysis process [32][33][34][35], interaction with DNA [36][37][38][39][40][41], the hydrogenbonding influence on the Pt-DNA adducts [42], and other aspects [43,44]. To clarify the preference of cisplatin for guanine over adenine, Baik et al [45] carried out DFT studies on the first substitution of cisplatin binding to purine bases.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin exerts its anticancer activity by forming 1,2-intrastrand cisplatin-DNA cross-links (Mantri et al, 2007;Yaneva et al, 2007;Harrington et al, 2010). However, a serious limitation in cancer chemotherapy with cisplatin is the development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%